Genetic variations associated with long noncoding RNAs. Issue 6 (7th December 2020) - Luo, Jianjun; Chen, Runsheng
Abstract: Genetic variations, including single nucleotide polymorphisms (SNPs) and structural variations, are widely distributed in the genome, including the long noncoding RNA (lncRNA) regions. The changes at locus might produce numerous effects in a variety of aspects. Multiple bioinformatics resources and tools were also developed for systematically dealing with genetic variations associated with lncRNAs. Moreover, correlation of the genetic variations in lncRNAs with immune disease, cancers, and other disease as well as development process were all included for discussion. In this essay, we summarized how and in what aspects these changes would affect lncRNA functions.